Institutional environment, firm ownership, and IPO first-day returns: Evidence from China - Chen, Yibiao; Wang, Steven Shuye; Li, Wei; Sun, Qian; Tong, Wilson H.S. (Journal of Corporate Finance, 2015)
We examine two inconclusive issues in the IPO (initial public offering) underpricing literature. It is unclear whether private firms or state-owned enterprises (SOEs) underprice their IPOs more and how the institutional environment affects IPO underpricing. Using a much larger China IPO sample of SOEs, we conclude that SOEs underprice their IPOs more than private firms. Specifically, SOEs controlled by the central government (CSOEs) underprice their IPOs 27 percentage points more than private firms, whereas SOEs controlled by local governments (LSOEs) underprice theirs 7 percentage points more than those of private firms. Using the National Economic Research Institute Index of Marketization (NERIIM) to measure the institutional environment, we find that one index score improvement in institutional environment is associated with a two percentage-point reduction in IPO underpricing. Importantly, a better institutional environment reduces IPO underpricing most effectively for private firms, followed by LSOEs, and the least for CSOEs.